Impact of Organizational Barriers, Inefficiencies, and Support on Digital Transformation: Perception on Quality 4.0 - Syafiqa, Suhaimi; Mohamad Reeduan, Mustapha; Shaik, Parvez (GBMR, 2023)
In this Quality 4.0 era, many organizations strived to implement and improve the efficiency of technology consumption in their organization. Modern technology is changing so rapidly that digital transformation is now widely understood. However, some organizations are still reluctant to start the transition as it could affect their ability to compete with others. This study aims to examine the impact of organizational barriers, inefficiencies, and support on digital transformation and to determine whether digitization can maintain or improve organizational performance. This study used a quantitative technique with a total of 89 respondents. The study method is quantitative through e-survey data collection analyzed with IBM SPSS 25 software. Multiple linear regression is used to analyze the result to achieve the objective stated. The results showed that most respondents felt that technology helped them build confidence in completing their tasks. However, some improvements are still needed to keep up with future technological advances, as some respondents still need more confidence in working with technology to complete their work. In addition, most respondents believe that competent employees with the required skills are the most crucial success factor of digital transformation in the organization.